Zoned and staged construction of an underground complex in Shanghai soft clay. (August 2017) - Li, Ming-Guang; Zhang, Zhong-Jie; Chen, Jin-Jian; Wang, Jian-Hua; Xu, An-Jun
Abstract: Construction of an underground complex in congested urban areas calls for excavation of a group of foundation pits, referred to as a pit complex, which are usually surrounded by existing facilities. In such circumstances, the safety of the pit complex and facilities during the construction are of great concern. This paper presents a case of an underground complex construction in Shanghai soft clay. A pit complex composed of two deep excavations was excavated for a Comprehensive Transport Hub (CTH) and a commercial retail area and pedestrian concourse known as South Square (SS), which were connected to an operating metro station and a railway station. During the excavation, potential deformation of metro tracks and railway tracks were expected due to extensive soil unloading. To safeguard the railway and the subway, a zoned and staged construction technology was proposed, in which several temporary partition walls were constructed in addition to necessary supporting structures, to allow the large-scale deep excavations to be divided into several independent small-scale excavations. This paper discusses the rational construction sequence of these excavations as well as reinforcement measures in detail. The construction technology was examined by extensive field data. It is found that the maximum horizontal displacement of diaphragm walls ranged between 0.05% H e and 0.4% H e, where H e is the excavation depth. The vertical displacements of the railway tracks were well controlled, whereas the metro tracks heaved significantly due to unloading effect.